Urgensi Pedoman Pemidanaan Demi Terwujudnya Putusan Hakim yang Berkeadilan - La Ode Faiki (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Judge's decision, which is fair Abstract: In order to create a good and fair judiciary, the most important thing is to build the law as an instrument of legal institutions in order to carry out its duties as a law enforcement institution. Good law is law that supports justice and equality without discrimination. One of the mechanisms used by law enforcement institutions is a system of providing sanctions for those who violate legal norms. If it is related to criminal law enforcement, what must be developed is the construction and formulation of statutory regulations regarding criminal impositions, or in other words, the formulation of sentences in addition to reducing the scope for subjectivity in judges' judgments. One of the judge's decisions that caused concern for most of the public was when the judge tried a murder case committed by Inspector General Ferdy Sambo and his subordinates. They were all charged with violating Article 340 of the Criminal Code, but the judge who tried their case imposed varying sentences. This is because: The formulation of punishment in the Criminal Code Article 340 does not explicitly determine it basic punishment for each role. Criminal impositions vary only based on the judge's subjective judgment and beliefs. The formulation of Article 340 in the Criminal Code is: